Penerapan Metode Customer Satisfaction Index untuk Pengukuran Kepuasan Layanan pada Biro Promosi dan Admisi UKDLSM - Vivie Deyby Kumenap; Lanny Sitanayah; Billy Fernando Oentomo (JOINTER : Journal of Informatics Engineering, 2023)
Universitas Katolik De La Salle Manado (UKDLSM) is a university located in Kairagi I, Kombos, Manado City, North Sulawesi. Since its establishment in 2000 until now, UKDLSM has 7 Faculties and 13 Study Programs. UKDLSM has 7 bureaus that have tasks according to their respective fields to become one of the driving components of the university. One of them is the Biro Promosi dan Admisi (BPA) which has the task of carrying out promotions and managing administration for prospective students/new students. BPA has carried out various duties and responsibilities, but the services of the BPA cannot be assessed by prospective new students who register. This is because there is no application to find out whether prospective new students who register with UKDLSM are satisfied or not with the services from BPA. One method for measuring satisfaction is the Customer Satisfaction Index (CSI). The satisfaction score of CSI is divided into five criteria, namely 0%-20% very dissatisfied, 21%-40% dissatisfied, 41%-60% quite satisfied, 61%-80% satisfied, and 81%-100% very satisfied. The application of the CSI method in an application can measure the satisfaction of prospective new students who register at UKDLSM. The sample used for this research is UKDSLM class 2021 students. The results of calculations using the CSI method will measure the satisfaction of prospective new students according to predetermined criteria. The final results obtained can help CPAs evaluate the services that have been provided to prospective new students.